Persian version of Patient-Reported Outcome Measure for Urethral Stricture Surgery (USS-PROM) Questionnaire, Validation and Adaptation Study - Tayyebi azar, Ali; Fallah-Karkan, Morteza; Hosseini, Mohammad Ali; Kazemzadeh Azad, Babak; Heidarzadeh, Abtin; Hosseini, Jalil (Urology Journal, 2020)
Purpose: The aim of the present study was translation, cross cultural adaptation and face validity evaluation of the Persian version of Patient-Reported Outcome Measure for Urethral Stricture Surgery (USS-PROM) Questionnaire. Materials and Methods: This study was assessed: translation, translation quality, reverse translation and comparison of the english version, Content validity, internal consistency and stability. Content validity presents by index of content validity (CVI) and the content validity ratio (CVR). Internal consistency reliability was tested by Cronbach’s ?, and test-retest reliability was evaluated by Intraclass Correlation Coefficient (ICC) assessed by Guttman two way mixed absolute agreements. Result: Frothy males with history urethroplasty and mean age of 41.4±9.08 (range of 19 to 52) years old; enrolled. In the case of mean scores of difficulty from the 16 translated items, 80% had easy translation. In terms of translation quality, 92% were the satisfactorily clear. In terms of similar concept, 92% were satisfactory. The overall quality of the translation was satisfactory at 88%. The translated questionnaire has a good internal consistency (Cronbach’s alpha as 0.84). CVI and the CVR, test-retest ICC evaluation were appropriate/acceptable in all questions. The questionnaire ICC was .791(CI 95%, .678-.876). Two main different aspects of the questionnaire consisted of urinary symptoms (question 1-10) and Quality of life (question 11-15) Cronbach’s alpha were .800 and .671 respectively. Conclusion: The Persian version of the questionnaire has acceptable cultural adaptation and face Validity. Further studies should be done using this translated tool to determine its applicability in the urethroplasty patients.